Cut foliage: potentiality of native Argentine ferns as new ornamental crops - Facciuto, Gabriela Rosa; Pannunzio, Maria Julia; Puerta, Analia Veronica; Sanchez, Marcela Ines (Sociedade Brasileira de Floricultura e Plantas Ornamentais, 2021)
The cut foliage constitutes an important part of the floricultural production since it represents a fundamental element in flower arrangements, and ferns are the complementary elements most used by florists. In Argentina, there is native material that has not been yet domesticated and could have suitable characteristics for foliage use. The objective of the work was to determine the potential use of 15 native ferns as cut foliage through quality parameters and vase life, generating a scoring system that allows a classification list. Morphological descriptors such as petiole length, length and width of the blade, planes in which the fronds are arranged, brightness, consistency, abundance of spores and presence of pests were taken into account. Also, the production of fronds of six selected species with good scores was recorded. The results showed that it is feasible to consider the commercial production of Pityrogramma calomelanos, Niphidium crassifolium, Campyloneurum nitidum, Blechnum austrobrasilianum and Pteris denticulata by the quantity of fronds obtained and their quality, represented by their size. Campyloneurum nitidum excelled for its vase life of more than 26 days and frond production of 273.61 fronds m-2 at second year cultivation. Pteris denticulata produces 179.44 fronds m-2 but vase life was only 7 days.